Organization of Learning Materials and Evaluation Learning Citizenship Education in College - Fawaidil Wafa, Alfian; Hanafi; Waliyuddin Fattah, Zulfikar (Indonesian Journal of Multidisciplinary Educational Research, 2024)
This research examines the evaluation of citizenship education learning. The method used in this research uses library research, which is a type of research that involves collecting data and information with the help of various kinds of materials available in libraries or on the internet that are related to the research topic. Data collection, processing and summarization are carried out systematically using techniques such as data reduction, data presentation, data verification and drawing conclusions. The organization of citizenship education learning materials must contain knowledge, values ​​and attitudes, as well as skills which are competencies that must be taught in citizenship education so as to produce citizens who are socially, spiritually and intellectually intelligent. Learning evaluation aims to find out how effective the application of knowledge and skills is in the real world or based on skill results.